STUDENTS’ PERCEPTION TOWARD INSTAGRAM USAGE IN WRITING SKILL - Manullang, Hana Elisabeth; Katemba, Caroline Victorine (ENGLISH JOURNAL, 2023)
The goal of this research is to describe students’ attitudes toward using Instagram to improve their writing ability and interest. In this study, the descriptive quantitative method was used. The information was gathered from senior high school students, and a total of 104 students took part. The goal of this study was to examine students’ perceptions of writing skills in using the Instagram application and as an English learning platform, as well as students’ understanding and interest in using Instagram application. Data were gathered using questionnaires distributed via Google Forms to high school students and interviews. For tallying the data analysis, the data analysis used SPSS and Excel software. This study finds that using Instagram can help senior high school students improve their writing skills.